PRODUK UNIT LINK UNTUK JOINT LIFE MENGGUNAKAN PENDEKATAN STOKASTIK - MURNIASIH, NI KETUT AYU; WIDANA, I NYOMAN; JAYANEGARA, KETUT (E-Jurnal Matematika; Vol 11 No 2 (2022)DO - 10.24843/MTK.2022.v11.i02.p368, 2022)
The insurance program has developed quite rapidly and the products that are displayed are only very attractive from protection products to protection and investment products known as unit link insurance. In general, unit-linked insurance products are offered with a death benefit for one person or single life. This study discusses unit link insurance with death benefits for two people or living together using profit testing calculations with a stochastic approach. This study aims to calculate the company's expectations of death benefits, profits and profits from unit link insurance for joint life using a stochastic approach. In this study, the ages of the participants of this unit link insurance are 35, 45, and 55. Premium payments of R p4.200 ,000.00 are made annually for 5 years and are covered until the age of 75 years. In the research, it is expected that the profit and death benefit using the stochastic approach are as follows: if the insured ages are 35, 45, and 55 years old, the company experiences a profit of Rp9,445,498,66, Rp5,975,926.42, and Rp2, respectively. 197,106.56 and the expected death benefit value is Rp. 33,167.00, Rp. 99,007.00 and Rp. 328.005.00, respectively.